Germany: on the verge of a new capitalist spirit? - Pohlmann, Markus; Fürstenberg, Alexander; Elias, Friederike (Global economic elites and the new spirit of capitalism, 2024)
The globalization discussion culminated, among other things, in the assumption that the old form of the nation-state, the national constitution of economy and society shall no longer play a decisive role and will be replaced by new, global forms of the economy (cf. e.g. Camilleri and Falk 1990; Narr and Schubert 1997; Ohmae 2010, cop. 1995). Narr/Schubert, for example, spoke of a denationalization of the economy (cf. Narr and Schubert 1997, 28 ff.) or others, like Altvater even of an “extreme de-territorialization of finance-driven capitalism”.
Gesehen am 27.06.2024